ESTIMASI BASIS POTENSI PAJAK RESTORAN DI KOTA BANDA ACEH - Taftazani Hulwani; M. Ilhamsyah Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
AbstractThis study aims to determine the large base tax potential (tax base) restaurant in Banda Aceh City. The method used is quantitative descriptive method by using primary data obtained from respondents in Banda Aceh City area which is randomly assigned as many as 35 respondents. Based on the result of research, the total weighted penerimaan potential is Rp. 9,684,073,410.44. The value of the potential weighted penerimaan is a value that reflects the potential penerimaan of the restaurant per month. This value is higher than the gross potential value, due to the standard error difference of each respondent. The total potential tax of restaurant is Rp.16.140.122.350,73. When compared with the total tax penerimaan in 2016, there is still a large enough difference from the potential of restaurant tax penerimaan. The implication of this research is that the object of cafe and coffee shop alone is still above the total income of restaurant tax in Banda Aceh City. Thus the policy makers in the city of Banda Aceh can optimize the tax penerimaan that comes from cafes and coffee shops.Keywords: Tax Base, Tax Potential, Restaurant Tax.